Merdeka Learning Campus Curriculum Design: A Review toward Islamic Banking Study Program in Universitas Islam 45 - Purnama Putra; Rizal Fahlevi; Rafika Rahmawati; Isfandayani Isfandayani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2023)
The development of Islamic Financial Institutions over the last few decades has experienced a significant increase. This increase should be followed by the provision of human resources that are useful as motors in these Islamic financial institutions. The Islamic Banking Department is one of the main partners in the Islamic finance industry in ensuring the availability of human resources. The curriculum that is used as learning outcomes must be synergized with the industrial world and market needs. A link and match synergy between higher education service providers with output in the form of competent graduates and the availability of jobs is urgently needed. Islamic University 45 with a major in Islamic banking carried out stages in designing a curriculum involving associations, representatives of Islamic financial institutions, representatives of Vocational Schools, Alumni and Experts in order to obtain a curriculum that is able to adapt to changes and market needs. The steps for compiling the curriculum are in accordance with systematic stages and reduce the gap between the world of education and the world of the Islamic finance industry.